2010
DOI: 10.1590/s0103-50532010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Constituents from Maytenus ilicifolia leaves and bioguided fractionation for gastroprotective activity

Abstract: Maytenus ilicifolia Mart. ex Reissek é tradicionalmente usada no Brasil para o tratamento de úlcera gástrica. O presente trabalho relata a investigação fitoquímica de um extrato etanólico de folhas de M. ilicifolia (EEMIL) visando o isolamento de constituintes que foram usados como marcadores químicos para monitorar o fracionamento de um extrato aquoso liofilizado de folhas de M. ilicifolia (LAEMIL). De EEMIL, quatro flavonóides foram isolados, compreendendo o triglicosídeo flavônico mauritianina (1), trifolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
0
19
0
5
Order By: Relevance
“…The plant is a small medicinal evergreen shrub that grows to a height of five meters bearing leaves and berries that resemble holly and is popularly known as "espinheira santa" (holy spine), "cancerosa", "cangorosa", "maiteno" and "espinheira divina" (divine spine) (Cordeiro et al, 2006). Maytenus ilicifolia is widely used as a traditional medicine in many countries of South America and its leaves are traditionally used as a remedy for gastrointestinal diseases, including dyspepsia and gastric ulcers (Leite et al, 2001(Leite et al, , 2010. They are found in the local commerce as capsules, powders, dried leaves, or as aqueous or aqueous-alcoholic preparations.…”
Section: Screening Of the Constituents From Maytenus Ilicifolia With mentioning
confidence: 99%
See 1 more Smart Citation
“…The plant is a small medicinal evergreen shrub that grows to a height of five meters bearing leaves and berries that resemble holly and is popularly known as "espinheira santa" (holy spine), "cancerosa", "cangorosa", "maiteno" and "espinheira divina" (divine spine) (Cordeiro et al, 2006). Maytenus ilicifolia is widely used as a traditional medicine in many countries of South America and its leaves are traditionally used as a remedy for gastrointestinal diseases, including dyspepsia and gastric ulcers (Leite et al, 2001(Leite et al, , 2010. They are found in the local commerce as capsules, powders, dried leaves, or as aqueous or aqueous-alcoholic preparations.…”
Section: Screening Of the Constituents From Maytenus Ilicifolia With mentioning
confidence: 99%
“…In a previous study, Baggio and collaborators reported the potent in vivo gastroprotective properties of a flavonoid-rich fraction separated from the leaves of Maytenus ilicifolia, Maytenus ilicifolia, containing epicatechin (3.1%) and catechin (2%) as major constituents, which was correlated with the in vitro inhibition of rabbit gastric H+,K+-ATPase activity (Baggio et al, 2007). Aiming to further the investigation on the bioactive constituents from Maytenus ilicifolia leaves, Leite et al, (2010) carried out a phytochemical investigation of an ethanol extract of Maytenus ilicifolia leaves for the isolation of compounds which were further used as chemical markers to monitorize an activity-guided fractionation of a lyophilized aqueous extract of Maytenus ilicifolia leaves. Finally, high performance liquid chromatography analyses of aqueous extract and its chromatographic fractions were carried out, aiming at establishing a correlation between gastroprotective effect and chemical composition.…”
Section: Screening Of the Constituents From Maytenus Ilicifolia With mentioning
confidence: 99%
“…É popularmente conhecida como espinheira-santa (holy spine), cancerosa, cangorosa, maiteno e espinheira divina (divine spine) 15 . A espinheira-santa é amplamente empregada na medicina tradicional em muitos países da América do Sul, suas folhas são comumente utilizadas como remédio para doenças gastrointestinais, incluindo dispepsia e úlceras gástricas 16 . Remédios com essa planta são encontrados no comércio local, com apresentação em cápsulas, pós, folhas secas, ou como preparações aquosas ou aquoso-alcoólicas.…”
Section: Introductionunclassified
“…Remédios com essa planta são encontrados no comércio local, com apresentação em cápsulas, pós, folhas secas, ou como preparações aquosas ou aquoso-alcoólicas. Ao analisar a composição química, a comprovada presença de metabólitos fenólicos, tais como taninos condensados, flavonoides e triterpenos 16 , poderia justificar o uso de algumas espécies de Maytenus como medicamento anti-inflamatório e no combate a úlceras. Essas funções são corroboradas cientificamente e abrem espaço para a utilização dessa tintura para esses agravos.…”
Section: Introductionunclassified
See 1 more Smart Citation